Annual World Bank Conference on Development Economics 1996 (The World Bank, 1997)
These articles, initially presented at the Annual World Bank Conference on Development Economics, held April 25-26, 1996, address four themes:banking failures as crises or opportunities for reform; reducing poverty through targeted programs and rural finance; legal systems and economic development; and labor and environmental standards in international trade. Although covering varied topics, the articles share two overarching themes:the shifting role for government in economic development, and the central role for government policy in each area as critical to development. The articles also focus on the role of institutions, the importance of political and economic competition, and the role of law and political organization. Several articles stress the vital role of institutions and related incentives in finance. These articles and the keynote address discuss the role of government as an institution, the balance between introducing competition within government and devolving government activities to the market, and the balance between deregulation and correction of market failures and the creation of markets. The authors note that political competition in bureaucracies may be an effective surrogate for market competition. Also discussed is the growing recognition that as income rises, so does demand for labor and environmental standards. Another article shows that linking environmental standards to trade will not achieve the goals sought by the standards and could disrupt trade. Multilateral organizations may have an important advocacy role in ensuring fair play in administering standards. The discussion on the role and the rule of law emphasizes the links between demand for law and the legal and political systems. Legal systems must be country or context specific:there is no unique, optimal combination of contract designs and enforcement mechanisms because culture plays an important role in the interaction of social.